Flaviviruses: Innate Immunity, Inflammasome Activation, Inflammatory Cell Death, and Cytokines - Pan, Yuhong; Cai, Wenjun; Cheng, Anchun; Wang, Mingshu; Yin, Zhongqiong; Jia, Renyong (Frontiers in Immunology, 2022)
The innate immune system is the first line of defense against pathogens including flaviviruses. Cell death plays an important role in limiting infection with pathogens. However, inflammatory cell death also results in the release of pro-inflammatory cytokines and cellular contents, which can cause severe inflammation. In this review, we focused on our current understanding of the innate immune response, inflammasome activation, inflammatory cell death pathways, and cytokine secretion during Dengue virus, West Nile virus, Zika virus, Japanese encephalitis virus and other flavivirus infections. We also discussed how the pathogenesis of these viruses affects these biological processes, which provides a scientific basis for understanding the pathogenesis of flavivirus and helps in developing effective antiviral therapies.